2013
DOI: 10.1021/nn4035525
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Copper Sulfide Nanoparticles into Nanoribbons with Continuous Crystallinity

Abstract: Copper chalcogenide nanoparticles (NPs) represent a promising material for solar energy conversion, electrical charge storage, and plasmonic devices. However, it is difficult to achieve high-quality NP dispersions in experimentally convenient and technologically preferred aqueous media. Also problematic is the transition from NP dispersion to continuously crystalline nanoscale materials, for instance, nanowires, nanoribbons, or similar high aspect ratio nano/microstructures capable of charge transport necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 76 publications
5
52
0
Order By: Relevance
“…Formatted ... [2] Formatted ... [3] Formatted ... [4] Formatted ... [5] Formatted ... [6] Formatted ... [7] Formatted ... [8] Formatted ... [9] Formatted ... [10] Formatted ... [11] Formatted ... [12] Formatted ... [13] Formatted ... [14] Formatted ... [15] Formatted ... [16] Formatted ... [17] Formatted ... [18] Formatted ... [19] Formatted ... [20] Formatted ... [21] Formatted ... [22] Formatted ... [23] Formatted ... [24] Formatted ... [25] Formatted ... [26] Formatted ... [27] Formatted ... [28] Formatted ... [29] Formatted ... [30] Formatted ... [31] Formatted ... [32] Formatted ... [33] Formatted ... [34] Formatted ... [35] Formatted ... [36] Formatted ... [37] Formatted ... [38] Formatted ... [39] Formatted ... [40] Formatted ... [41] The surface PEGylation rendered copper sulfide NPs excellent colloidal stabilities in both water and PBS buffer apart from significant LSPR effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formatted ... [2] Formatted ... [3] Formatted ... [4] Formatted ... [5] Formatted ... [6] Formatted ... [7] Formatted ... [8] Formatted ... [9] Formatted ... [10] Formatted ... [11] Formatted ... [12] Formatted ... [13] Formatted ... [14] Formatted ... [15] Formatted ... [16] Formatted ... [17] Formatted ... [18] Formatted ... [19] Formatted ... [20] Formatted ... [21] Formatted ... [22] Formatted ... [23] Formatted ... [24] Formatted ... [25] Formatted ... [26] Formatted ... [27] Formatted ... [28] Formatted ... [29] Formatted ... [30] Formatted ... [31] Formatted ... [32] Formatted ... [33] Formatted ... [34] Formatted ... [35] Formatted ... [36] Formatted ... [37] Formatted ... [38] Formatted ... [39] Formatted ... [40] Formatted ... [41] The surface PEGylation rendered copper sulfide NPs excellent colloidal stabilities in both water and PBS buffer apart from significant LSPR effect.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In addition, its size-dependent NIR absorption behavior in small size regime (<10 nm) favors the in vivo bioapplications for tumor imaging. [27][28][29] Nevertheless, due to the inherent dipole-dipole interaction, strong interactions among the NPs often lead to particle aggregation. Up to now, the synthesis of water-soluble copper sulfide NPs is mainly achieved through two synthetic routes: indirect organic-phase synthesis followed by a ligandexchange process, and direct aqueous-phase synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The ease of the compressive process facilitates fundamental understanding of nanomaterial coupling through energy transfer. We envision that this method could apply to a variety of other semiconductor and magnetic materials ( 35 , 36 ). …”
Section: Discussionmentioning
confidence: 99%
“…It has been seen that the average of mean diameters of the Cu NPs supported on Cu-2TPABTz is 4.7 nm (Fig. 53 More specically, as shown in Fig. 36,48 Likewise, it is found that critical particle sized Cu NPs (around 4.7 nm) embedded in Cu-2TPABTz display excellent photocatalysis aermentioned.…”
mentioning
confidence: 83%